Antibiotic Consumption Patterns in Urban Coari, Amazonas: High Azithromycin Use and COVID-19-Related Prescriptions - Rodrigo Silva Marcelino; Edivã Bernardo da Silva; Abel Santiago Muri Gama; Ananias Facundes Guimarães; Silvia Regina Secoli; Albert Figueras (Pharmacoepidemiology)
Background/Objectivses: Antibiotic consumption patterns in remote urban areas of the Amazon region are poorly understood. This study aimed to analyze antibiotic use in the adult population of Coari, a municipality in Amazonas, Brazil. Methods: A cross-sectional study was conducted between October and November 2021 in the urban area of Coari. 394 adults were interviewed using a structured questionnaire. Data on antibiotic use, sociodemographic factors, health service access, and self-reported illnesses were collected. Poisson regression was used to estimate prevalence ratios and identify factors associated with antibiotic use. Results: The prevalence of antibiotic use was 14.7% (n = 58). The most frequently used antibiotics were azithromycin (26.9%), cefalexin (20.9%), amoxicillin (19.4%), and ciprofloxacin (13.9%). Up to 34.5% of antibiotic use was conducted without a prescription, especially among adults aged 18 to 39 (59.1%). The main health problems that led to self-medication were COVID-19 (28.6%), urinary infection (14.3%), sore throat (37.5%), and intestinal infection (60.0%). Factors associated with antibiotic use included age 18 to 39 (adjusted PR = 3.73; CI = 1.37–10.09), having a family member hospitalized (adjusted PR = 2.61; CI = 1.39–4.89), having contracted COVID-19 (adjusted PR = 2.41; CI = 1.40–4.15), and frequency of visits by the community health agent to the home (adjusted PR = 0.35 CI = 0.15–0.81). Conclusions: The high use of broad-spectrum antibiotics (Watch), particularly azithromycin, for potentially inappropriate indications highlights the need to improve the management of antibiotic use in remote regions of Brazil. Community health agents, as key professionals between health services and the community, can play a key role in promoting the rational use of antibiotics and combating antimicrobial resistance in the Brazilian Amazon context.